The Decision of Problems of Optimization of Territorial Arrangement of the Radio-Transmitting Stations at Design of Transmission Networks - Ščerbakov, G. I.; Lindval, V. R.; Spirina, E. A.; Letaiaf, M. A. (Elektronika ir Elektrotechnika, 2004)
Nowadays telecommunication systems, including television and radio ones, are progressing intensely. Their further developmentneeds handling the problem of an electromagnetic compatibility between all the radio-transmitting stations located in a certain territoryand operating in common or adjacent frequency bands. To launch a new station or improve the performance of existing one, as a rule,some correction of characteristics of other stations needs to be done. This is why effective planning a network as a whole is of particularimportance for rational use of its potentialities. The article is devoted to the problem of optimum planning broadcast networks withrespect of best covering a determined territory at the minimal technical resources. Examples of such a solution computing by authors’program complex “Resource” are given. Ill. 7, bibl. 5 (in Russian; summaries in English and Russian).